Analisis Dampak Penyelenggaraan Kota Sehat terhadap IPM Kota Banjarmasin Tahun 2010-2017 - Diba, Farah; Saipudin (PPJP ULM, 2019)
This study aims to determine the impact of Healthy Cities' implementation onBanjarmasin City HDI from 2010 to 2017 to find out how the effect of implementinghealthy cities on HDI in Banjarmasin City as a first step in taking policies related tothe implementation of healthy cities.This study's scope was to analyze the impact of the implementation of ahealthy city on the Banjarmason HDI in 2010-2017. The use of data analysistechniques in this study is descriptive, namely collecting, dividing, and decipheringthe data obtained. The objective results obtained from the problem of an analysis ofthe effects of monitoring data.This study indicates that the implementation of a healthy city has a positiveimpact on increasing the Human Development Index in Banjarmasin City. This can beseen from the increase in the Human Development Index of Banjarmasin City fromyear to year. Organizing healthy cities can also make health services better from yearto year and can be felt well by the community.